An Interview-Based Approach to Elicit User Interface Design for Web Applications - Atikah Shamat, Nur; Sulaiman, Shahida; Sudah Sinpan, Jacline (International Journal of Engineering and Technology, 2018)
Elicitation of user interface design for Web applications is a process to gather precise information from users to aid software engineers in designing the user interface according to usersâ€™ wants and needs. There are several issues that are related to the user interface design if they do not fulfill usersâ€™ expectations. For instance, software engineers misunderstand what users need and lack of information from users about the requirements to design the user interfaces. Thus, the elicitation of user interface design is vital in order to reduce the problem especially for Web applications. This research proposes an interview-based approach to elicit user interface design for Web applications. A prototype tool has been developed to help software engineers elicit the user interface requirements from users precisely. The evaluation shows that the proposed approach has the possibility to reduce the misunderstanding in user interface design with the focus on input control elements.Â Â